7(x-2)-8(4-3x)=2x-1

Simple and best practice solution for 7(x-2)-8(4-3x)=2x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-2)-8(4-3x)=2x-1 equation:



7(x-2)-8(4-3x)=2x-1
We move all terms to the left:
7(x-2)-8(4-3x)-(2x-1)=0
We add all the numbers together, and all the variables
7(x-2)-8(-3x+4)-(2x-1)=0
We multiply parentheses
7x+24x-(2x-1)-14-32=0
We get rid of parentheses
7x+24x-2x+1-14-32=0
We add all the numbers together, and all the variables
29x-45=0
We move all terms containing x to the left, all other terms to the right
29x=45
x=45/29
x=1+16/29

See similar equations:

| d-19=35 | | N=m-14m= | | 3x=2x-1=8 | | 80-5x=30 | | 4^3y-5=6^y+2 | | 4p–2=10 | | 32+35+x=108 | | 24x-13=24 | | P(x)=18000(1-0.012)^x | | 5×-3y=11 | | ×{5×-3y=11 | | 60-3x=15 | | 16=35/6x-34 | | 5+10=4x+3 | | t-25=50 | | 9l+2=29 | | 12x^2-8-x=0 | | 5m+7-37=-25 | | -9x+7=178 | | −8x+13=−10x–19 | | 6x=10x+6x | | 3x+2/x-6=-8 | | -3x-7=50 | | 6x=10+6 | | 0=4u+18 | | 16=19x+5 | | 10x-5-2(3x+1)=100 | | 4+9=4x+5 | | -1=-4-n | | 0x2−19x+35=0 | | m/10=20 | | 10+n/10=13 |

Equations solver categories